A kind of fiber silky masterbatch composition and its preparation method and application
By using a mixture of saturated alkane primary amide and alkane secondary amide as a slip agent, and combining other materials to prepare a fiber silky masterbatch composition, the problem that polypropylene fibers are difficult to maintain long-term silky stability is solved, and high-quality and stable fiber products are achieved.
Patent Information
- Application Number
- CN202310432375.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-04-21
AI Technical Summary
The prior art is difficult to make polypropylene fibers have long-term silky stability, and the added small molecule substances such as erucic acid amide are easily oxidized and degraded, affecting product quality stability.
A mixture of saturated alkane primary amide and alkane secondary amide is used as a slipper, combining olefin polymers, inorganic silicones, fluorine compounds, polyethylene glycols and antioxidants to prepare a fiber silky masterbatch composition through specific ratios and processes.
The fiber has a silky feel and maintains long-term stability, avoids oxidative degradation problems, and improves the quality stability and application range of the product.
Smart Images

Figure BDA0004190736340000021 
Figure BDA0004190736340000081 
Figure BDA0004190736340000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber nonwoven fabric processing and application, and in particular to a fiber silky masterbatch composition and a preparation method and application thereof. Background Art
[0002] Polypropylene materials can be made into fiber materials through a tiny extrusion die. Polypropylene fibers are widely used in packaging, filtration, decoration, beauty and other fields. Since polypropylene is a highly crystalline material, the products made into fibers are relatively hard and have a rough feel. By adding functional additives, the rough feel of polypropylene fibers can be effectively improved, and the scope of application can be broadened.
[0003] The prior art reports that the smooth feel of polypropylene fiber can be improved by adding erucamide, and that polypropylene fiber can be made by adding soft masterbatch (ethylene-propylene rubber, erucamide or oleamide and PPA processing aid) to obtain non-woven fabrics with good feel. The above two types of products are fiber products that obtain a soft effect by utilizing the smooth effect of erucamide and modifying polypropylene. The fibers obtained by these methods are indeed smoother than conventional fiber products. On the one hand, the addition of small molecules such as erucamide and oleamide will quickly migrate to the fiber surface to provide a smooth effect, but because they contain double bonds, oxidative degradation will occur during the production and processing and storage of finished products, which not only affects the stability of product quality, but also their rapid migration effect easily causes the fiber surface to become sticky, and loses the smooth effect.
[0004] Therefore, how to make polypropylene fiber have a smooth feel and maintain its silky stability for a long time is a problem that needs to be solved urgently at this stage. Summary of the invention
[0005] In order to overcome the above-mentioned defects of the prior art, the present invention proposes a fiber silky masterbatch composition and a preparation method and application thereof. The specific technical scheme is as follows:
[0006] A fiber silky masterbatch composition, comprising the following components in parts by weight:
[0007]
[0008] Wherein, the lubricant is a mixture of saturated alkane primary amide and alkane secondary amide.
[0009] Further, the olefin polymer is a homopolymer or copolymer of any one or more of ethylene, butene, octene and propylene, or a polyolefin elastomer, and preferably the olefin polymer is a homopolymer or copolymer of any two of ethylene, butene, octene and propylene, or a polyolefin elastomer. The melting point of the olefin polymer is 60-100° C. When the melting point is lower than 60° C., the viscosity of the copolymer increases, resulting in a decrease in the silky effect of the fiber product, while if the melting point is too high, the product has a high crystallinity, which has a certain effect on the softness.
[0010] Further, the saturated alkane primary amide can be selected from one or more of stearic acid amide, lauric acid amide, arachidic acid amide, behenic acid amide or palmitic acid amide, and the alkane secondary amide can be selected from one or more of octadecyl stearic acid amide, ethylene bislauric acid amide, ethylene bisbehenic acid amide, stearyl erucic acid amide and oleyl palmitic acid amide. The present invention is not limited thereto.
[0011] Preferably, the melting point of the lubricant is 60-120°C. If the melting point of the lubricant is too high, although the heat resistance stability is improved, it has a certain negative impact on the silky effect. By adding an olefin polymer with a specific melting point, or adding a lubricant with a specific melting point, or controlling the ratio of the lubricant, the feel and long-term stability of the fiber masterbatch composition can be further improved.
[0012] Preferably, the weight ratio of the saturated alkane primary amide to the alkane secondary amide is 3:(0.5-10); preferably 3:(1-9). By adjusting the compounding ratio of the saturated alkane primary amide to the alkane secondary amide, the silky effect and the long-term stability of the silky effect can be better balanced. The present invention is not limited to this.
[0013] Further, the inorganic silicon is one or more of silicon dioxide or silicates; further preferably, the sphericity of the inorganic silicon is greater than 95%, the D50 particle size of the inorganic silicon is 1-2um, and the D98 particle size of the inorganic silicon is less than 5um. The silicates are soluble silicates, and the soluble silicates are one or more of sodium silicate, potassium silicate and sodium metasilicate. The present invention is not limited thereto.
[0014] Furthermore, the fluorine compound is a polymer of any two or three of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene, and the Mooney viscosity of the fluorine compound is greater than 60, which can further improve the stability of the processing process and make it suitable for scene environments with more stringent requirements on stability.
[0015] It should be noted that in the present invention, there is no special restriction on the molecular weight of polyethylene glycol. The present invention mainly utilizes the good biocompatibility of polyethylene glycol after combining with other polymers, which can improve the softness, elasticity and toughness of the fiber masterbatch composition. Generally, the viscosity-average molecular weight of the polyethylene glycol is between 300,000 and 1,000,000; preferably, the viscosity-average molecular weight of polyethylene glycol is 1,000 to 1,000,000; further preferably, the viscosity-average molecular weight of polyethylene glycol is 5,000 to 1,000,000. Polyethylene glycol is a flexible long-chain polymer, which can improve the softness, elasticity and toughness of the fiber masterbatch composition after combining with other polymers. The viscosity-average molecular weight of polyethylene glycol can be adjusted to below the lower limit to the upper limit by appropriately adjusting the type and degree of polymerization of the monomer units constituting the polyethylene glycol.
[0016] Furthermore, the nucleating agent is a β-crystal nucleating agent.
[0017] Specifically, the β-crystal nucleating agent may be one or more of an aromatic amine nucleating agent, a rare earth complex nucleating agent, a quinoline acridone nucleating agent, a condensed ring compound nucleating agent, and a composite nucleating agent. The present invention is not limited thereto.
[0018] Furthermore, the antioxidant is a compound of a conventional amine main antioxidant and a phosphite antioxidant. The weight ratio of the conventional amine main antioxidant to the phosphite antioxidant can be (1-2): 1. The present invention selects suitable varieties and dosages from different varieties of antioxidants, and the selected antioxidants produce antioxidant synergistic effects, so that the antioxidants used in the fiber silky masterbatch composition have better cost performance, and can prevent or reduce oxidative degradation during production and processing and storage of finished products. The present invention is not limited to this.
[0019] The present invention also provides a method for preparing the above-mentioned fiber silky masterbatch composition, comprising the following steps:
[0020] S1: Weigh the components according to the ratio, and prepare a pre-dispersion by mixing the lubricant, inorganic silicon, fluorine compound, polyethylene glycol, nucleating agent and antioxidant;
[0021] S2: The pre-dispersion of step S1 and the olefin polymer are subjected to metering, extrusion, dispersion and granulation through a screw to obtain the fiber silky masterbatch composition.
[0022] Furthermore, step S1 is specifically as follows:
[0023] (1) Weigh each component according to the ratio, first add the lubricant, polyethylene glycol and antioxidant into a closed stirring kettle with a heating and cooling device, set the temperature to 100-130° C., heat up, stir slowly while heating, and continuously introduce inert gas;
[0024] (2) After the temperature reaches the set temperature of 100-130°C, add inorganic silicon, fluorine compound and nucleating agent, stir, and keep the inert gas filled. After stirring for 1-3 hours, cool to room temperature through cooling circulating water;
[0025] (3) The cooled mixture is in a solid state, and is put into a mixing device for further mixing and dispersion to ensure that the particle size after mixing is less than 6 mm, thereby preparing the pre-dispersion.
[0026] Furthermore, in step S2, the pre-dispersion obtained in step S1 and the softener are metered, extruded, dispersed and granulated by a screw, and the particle size of the fiber silky masterbatch composition is controlled to be between 2-5 mm during granulation.
[0027] The present invention also provides the use of the above-mentioned fiber silky masterbatch composition in the preparation of fiber products, such as non-woven fabrics, etc. When used, 5-10wt% of the fiber silky masterbatch composition is added to polypropylene melt extrusion spinning or non-woven fabric manufacturing equipment to manufacture fiber products.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The invention prepares a masterbatch composition which can make the fiber have a silky feel and maintain long-term silky stability by adding a specific lubricant composed of saturated alkane primary amide and alkane secondary amide. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] <Preparation of Examples and Comparative Examples>
[0032] The equipment and instruments used in the embodiments of the present invention and the comparative examples are as follows:
[0033] Reactor, 100L Yantai Tengao Chemical Machinery Co., Ltd.;
[0034] Twin-screw extruder, Coperion (Nanjing) Machinery Co., Ltd., length-to-diameter ratio 40:1;
[0035] Mixer, SHR400L Zhangjiagang Yili Machinery;
[0036] Non-woven fabric testing machine, Zibo Fangchen Masterbatch Factory Co., Ltd.;
[0037] Fabric strength tester, Wuhan Guoliang Instrument;
[0038] Fabric softness tester GL005, Wuhan Guoliang Instrument;
[0039] Friction coefficient tester, NW258, Quanzhou Meibang Instrument Co., Ltd.
[0040] The raw materials used in the examples and comparative examples of the present invention are all commercially available, but are not limited to these materials:
[0041] Olefin polymer A: propylene-ethylene polymer, melting point 60°C, brand VISTAMAXX 6102, purchased from ExxonMobil;
[0042] Olefin polymer B: propylene polymer, melting point 100°C, brand LICOCENE PP2602, purchased from Clariant Chemicals;
[0043] Olefin polymer C: ethylene-octene copolymer, melting point 55°C, brand ENGAGE 8137, purchased from Dow Chemical;
[0044] Olefin polymer D: ethylene polymer, melting point 125°C, grade LLDPE M2320, purchased from Maoming Petrochemical;
[0045] Lubricant:
[0046] Saturated alkane primary amide: stearic acid amide, melting point 108.5-109°C, brand S861460, purchased from Shanghai Macklin;
[0047] Alkane secondary amide: stearyl erucic acid amide, melting point 65-85°C, brand name chemide SEA, purchased from Hengchang, Changsha, Hunan;
[0048] Erucamide, commercially available;
[0049] Oleamide, commercially available;
[0050] Silicon dioxide: brand RD20, purchased from Jiangsu Jinyi New Materials;
[0051] Silicates: spherical aluminosilicate, brand RDZ052, purchased from Jiangsu Jinyi New Materials;
[0052] Polyethylene glycol: viscosity average molecular weight of 700,000, brand P815466, purchased from Shanghai McLean;
[0053] Fluorine compound: brand PPA 3511 (copolymer of vinylidene fluoride and hexafluoropropylene), purchased from Guangzhou Energy;
[0054] Nucleating agent: β-crystalline nucleating agent, brand NA-82, purchased from Guangzhou Chenghe Technology;
[0055] Antioxidant: Amine main antioxidant and phosphite antioxidant are compounded, antioxidant 1019 and antioxidant 168 are compounded in a ratio of 1:1, commercially available;
[0056] Polypropylene: brand S2040, purchased from Shanghai Secco.
[0057] The preparation methods of Examples 1-15 and Comparative Examples 1-8 of the present invention are as follows:
[0058] S1: Weigh each component according to the ratio, first add the lubricant, polyethylene glycol and antioxidant into a closed stirring kettle with a heating and cooling device, set the temperature to 125°C, heat up, stir slowly while heating, the stirring speed is 80 rpm, and continuously introduce and fill with nitrogen;
[0059] After the temperature reaches 125°C and the mixture is stirred at a constant temperature for 10 minutes, the inorganic silicon powder, fluorine compound and nucleating agent are added, the rotation speed is increased to 300 rpm and stirred rapidly, and the nitrogen is kept full. After stirring for 1 hour, the reactor is cooled to room temperature by cooling circulating water, and then the nitrogen is stopped and the sample is discharged;
[0060] The cooled mixture is in a solid state and is put into a mixing device for further mixing and dispersion. The mixer speed frequency is set to 40 Hz and mixed continuously for 5 minutes to ensure that the particle size after mixing is less than 6 mm. The pre-dispersion is obtained by discharging the sample.
[0061] S2: The pre-dispersion and softener of step S1 are metered, extruded, dispersed and granulated by a screw. The aspect ratio of the extruder is 40:1. The set temperatures of zones 1-10 are 50°C, 100°C, 130°C, 130°C, 130°C, 120°C, 120°C, 120°C, 120°C, 130°C, the extrusion speed is 300 rpm, the feed rate is 150 kg / hour, the particle size is controlled at 2-5 mm, and a fiber silky masterbatch composition is obtained.
[0062] <Test Standard>
[0063] 500 g of the silky masterbatch prepared in the embodiment and the comparative example were respectively mixed evenly with 4500 g of polypropylene resin, and put into a non-woven fabric sample making machine for sample making. The temperatures of zones 1-6 of the sample making machine were set to 180°C, 220°C, 220°C, 220°C, 225°C, and 230°C, the temperature of the metering pump housing was 225°C, the temperature of the spinneret zone was 225°C, the speed of the metering pump was 35HZ / min, the air volume of the measured blowing was controlled to be 750 rpm, the temperature was set to 18°C, the filaments sprayed from the spinneret were stretched and laid on a conveyor belt, the conveyor belt speed was adjusted to control the weight to be 30±1g, the upper and lower rollers of the traction roller were set to temperatures of 125°C and 120°C, respectively, and the pressure was 10N.
[0064] The prepared fiber samples were stored in an environment of 23°C and 50% relative humidity for 3 days before measuring tensile strength, friction coefficient, softness index and color difference. The friction coefficient was tested by rubbing two identical fiber cloths against each other. The tensile strength and softness index values were measured by taking the arithmetic mean of 5 samples in the longitudinal and transverse directions. The friction coefficient and color difference were measured by randomly sampling 5 samples and taking the arithmetic mean.
[0065] Performance test standards / methods:
[0066] Weight: measured according to FZ / T6003-1991 method;
[0067] Tensile strength: tested according to ASTM D5034-09 (2017) standard;
[0068] Softness: Test according to GB / T 3854-2017 standard. Place the sample on a hard and stable support surface, place the HBa-1 Barcol hardness tester on the surface of the sample to be tested, make the indenter perpendicular to the surface of the sample to be tested, hold the hardness tester housing, and push it steadily and quickly with a pressure of 4 kg. At the same time, record the maximum reading on the dial and take the average value. The higher the reading of the Barcol hardness tester, the greater the hardness.
[0069] Friction coefficient: tested according to ASTM D1894-2008 standard;
[0070] Color difference: tested according to CIE LAB standards;
[0071] Sensory touch: Soft and silky touch is judged as excellent, moderately soft or silky touch is judged as good, and hard touch or no smooth feeling is judged as poor.
[0072] Table 1. Examples 1-10 formulations (parts by weight)
[0073]
[0074] Table 2. Formula of Examples 11-15 (parts by weight)
[0075]
[0076]
[0077] Table 3. Performance test results of Examples 1-10
[0078]
[0079] Table 4. Performance test results of Examples 11-15
[0080]
[0081]
[0082] Table 5. Comparative Examples 1-8 formulations (parts by weight)
[0083]
[0084] Table 6. Performance test results of comparative examples 1-8
[0085]
[0086]
[0087] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that the lubricant in the components of Comparative Example 1 is 10 parts by weight, and the lubricant component is erucamide (cis-13-docosahexaenoic acid amide) and oleamide (cis-9-octadecenoic acid amide, which is an unsaturated fatty amide) compounded in a weight ratio of 1:1, and the rest is the same as Example 1, and the prepared fiber feels obviously hard.
[0088] Compared with Example 1, Comparative Examples 2-6 do not add lubricants, inorganic silicon powders, fluorine compounds, polyethylene glycol or nucleating agents, which will have a negative impact on the softness of the fiber, increase the friction coefficient of the fiber, increase the color difference, feel hard or sticky, and have no smooth feel.
[0089] Compared with Example 1, in Comparative Examples 7 and 8, the lubricant is not compounded, but all stearic acid amide or all stearyl erucic acid amide is used. The softness of Comparative Examples 7 and 8 deteriorates, the friction coefficient increases, the color difference is serious, and the sensory tactile effect deteriorates.
[0090] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A fiber silky masterbatch composition, characterized in that: By weight, it includes the following components: Wherein, the lubricant is a mixture of saturated alkane primary amide and alkane secondary amide; The weight ratio of the saturated alkane primary amide to the alkane secondary amide is 3:(0.5-10).
2. The fiber silky masterbatch composition according to claim 1, characterized in that: The olefin polymer is any one or more homopolymers or copolymers of ethylene, butene, octene and propylene, or a polyolefin elastomer; the melting point of the olefin polymer is 60-100°C.
3. The fiber silky masterbatch composition according to claim 1, characterized in that: The melting point of the lubricant is 60-120°C.
4. The fiber silky masterbatch composition according to claim 1, characterized in that: The weight ratio of the saturated alkane primary amide to the alkane secondary amide is 3:(1-9).
5. The fiber silky masterbatch composition according to claim 1, characterized in that: The inorganic silicon is one or more of silicon dioxide or silicates.
6. The fiber silky masterbatch composition according to claim 1, characterized in that: The fluorine compound is a polymer of any two or three of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene.
7. The fiber silky masterbatch composition according to claim 1, characterized in that: The nucleating agent is a β-crystal nucleating agent.
8. The fiber silky masterbatch composition according to claim 1, characterized in that: The viscosity average molecular weight of the polyethylene glycol is between 300,000 and 1,000,000.
9. The fiber silky masterbatch composition according to claim 1, characterized in that: The saturated alkane primary amide is selected from one or more of stearic acid amide, lauric acid amide, arachidic acid amide, behenic acid amide or palmitic acid amide; The alkane secondary amide is selected from one or more of octadecyl stearic acid amide, ethylene bislauric acid amide, ethylene bisbehenic acid amide, stearyl erucic acid amide and oleyl palmitic acid amide.
10. A method for preparing the silky fiber masterbatch composition according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weigh the components according to the ratio, and prepare a pre-dispersion by mixing the lubricant, inorganic silicon, fluorine compound, polyethylene glycol, nucleating agent and antioxidant; S2: The pre-dispersion of step S1 and the olefin polymer are subjected to metering, extrusion, dispersion and granulation through a screw to obtain the fiber silky masterbatch composition.
11. Use of the fiber silky masterbatch composition according to any one of claims 1 to 9 in the preparation of fiber products.
Citation Information
Patent Citations
Thin film processing-assisting master batch composition and preparation method thereof
CN115572431A
Thermoplastic resin composition comprising a mixture of slip agents and a mono-or co-extruded, laminated or non-laminated film
US20130345349A1